Production and fluxes of inorganic carbon and alkalinity in a subarctic subterranean estuary - Chaillou, Gwénaëlle; Tommi-Morin, Gwendoline; Mucci, Alfonso (Frontiers in Marine Science, 2024)
In this study, we focus on the biogeochemical processes that produce both dissolved inorganic carbon (DIC) and total alkalinity (TA) along a subarctic subterranean estuary (STE) located in the Gulf of St. Lawrence (Magdalen Island, Qc, Canada) in order to evaluate the DIC and TA fluxes as well as the buffering capacity of the exported groundwater to coastal waters. DIC and TA do not behave conservatively during mixing along the groundwater flow path and this implies the occurrence of internal redox reactions that control both their production and consumption. In addition, we show that the origin and composition of the organic carbon within the system alter the carbonate parameters by generating low pH conditions (5.9 - 7.2) and contributing to non-carbonate alkalinity (NCA) that accounts for more than 30% of TA. Whereas iron cycling plays a key role in the production of DIC in the fresh and low-salinity groundwaters, the precipitation of sulfide minerals neutralize the acidity produced by the metabolically produced CO2, in the saline groundwater where sulfate is available. The STE pCO2, computed from the DIC-pHNBS pair ranged from a few ppm to 16000 ppm that results in a CO2 evasion rate of up to 310 mol m−2d−1 to the atmosphere. Based on Darcy flow and the mean concentrations of DIC and carbonate alkalinity (Ac = TA - NCA) in the discharge zone, fluxes derived from submarine groundwater discharge were estimated at 1.43 and 0.70 mol m−2d−1 for DIC and Ac, respectively. Despite a major part of the metabolic CO2 being lost along the groundwater flow path, the SGD-derived DIC flux was still greater than the Ac flux, implying that groundwater discharge reduces the buffering capacity of the receiving coastal waters. This site-specific scale study demonstrates the importance of diagenetic reactions and organic matter remineralization processes on carbonate system parameters in STE. Our results highlight that subarctic STEs could be hot spots of CO2 evasion and a source of acidification to coastal waters that should be considered in carbon budgets.